Παρατηρήσεις επί της ανεκδότου ακολουθίας του Οσίου Λουκά του εν Σικυωνι - ΑΝΑΓΝΩΣΤΟΥ, Μυρσίνη (Byzantina Symmeikta, 2020)
Comments on the Previously Unknown Acolouthy of Saint Lukas of Sikyon Cod. Sinaiticus gr. 568, ff. 32v-36v includes an, until recently, unknown acolouthy dedicated to the life of Saint Lukas of Sikyon. This paper aims at presenting this text, and revealing the new findings that arise from its study. Furthermore, an effort is made to identify Saint Lukas of Sikyon with Saint Lukas of Tauromenion. The text offers an interesting description of the life of a saint whose feast ceased to be commemorated throughout the years. The previously unknown acolouthy and vita found in the Synaxarion of Constantinople are used as sources for the narration of the saint’s life. It is, however, worth mentioning that the acolouthy offers new information about the life of the saint which is not included in his vita.